Imaging anatomy. text and atlas - Saremi, Farhood; Sánchez-Quintana, Damián (Thieme, 2023)
"Normal imaging anatomy and variants, including diagnostic and surgical anatomy, are the cornerstones of radiologic knowledge. Imaging Anatomy: Text and Atlas Volume 2, Abdomen and Pelvis is the second in a series of four richly illustrated radiologic references edited by distinguished radiologist Farhood Saremi. The atlas is coedited by esteemed colleagues Damián Sánchez-Quintana, Hiro Kiyosue, Dakshesh B. Patel, Meng Law, and R. Shane Tubbs with contributions from an impressive cadre of international authors. Succinctly written text and superb images provide readers with a virtual, user-friendly dissection experience"--